Creative Teachers in Teaching Speaking Performance - Anton Setiawan; Ahmad Munir; Suhartono Suhartono (Jurnal Pedagogy, 2019)
Creativity has an important role in teaching process. However, the students’ achievement are not realeased by the role of creative teachers. This study aims at exploring some factors that used by creative teachers in teaching speaking performance. As media and strategies are the crucial factors that used by the teachers to help the students understand the material easily. The qualitative study was applied in this research. The technique of collecting the data was an interview, and questionnaire from the English teachers in five schools in Surabaya. This study found that there were some factors that influenced the creative teachers in teaching speaking performance such as (1) media usage: powerpoint presentation, chunks of familiar pictures, attention-grabbing pictures, music ball, and eye-catching cup as well as some online exercise links; (2) strategies election: by performing ball and cup moving, “boom” counting, guessing game, chained word game and listening comprehension taken from Google translate recording; (3) lesson plan; (4) organize the material. In conclusion, the creative teachers applied some factors in teaching speaking performance to enhancing students speaking performance.